Analisis Eko-Hidrologi Spasial untuk Rekomendasi Pengembangan Berkelanjutan di Taman Wisata Alam Talaga Bodas - Adiyaksa, Narendra Bagus; Kendarto, Dwi Rustam; Firmansyah, Indra (Syntax Literate, 2025)
Talaga Bodas Nature Park is a volcanic ecotourism area vulnerable to degradation if not managed sustainably. This study aims to develop a sustainable development strategy based on a spatial eco-hydrological approach. This approach integrates NDVI (Normalized Difference Vegetation Index) satellite imagery analysis, erosion estimation using the RUSLE (Revised Universal Soil Loss Equation) method, and strategy formulation using the Analytical Hierarchy Process (AHP). The results show that most areas in Talaga Bodas have moderate to low NDVI values and erosion rates ranging from very light to very severe. The degradation of vegetation and high erosion potential is suspected to be related to uncontrolled tourism activity. AHP-based strategy priorities indicate that zoning regulation, local community involvement, and environmentally-based tourism development are the main strategies for sustainable development in Talaga Bodas. This study highlights the importance of an integrated eco-hydrological approach in managing ecologically vulnerable nature tourism areas.